Comparison of mindfulness interventions for healthcare professionals: A mixed-methods study. (November 2022) - Morrow, Ellen H.; Mai, Trinh; Choi, Bom; Gu, Lily Y.; Thielking, Paul; Sandweiss, David; Qeadan, Fares
Abstract: Objectives: Burnout is increasingly a concerning problem in US Healthcare systems. Although the causes of burnout are not predominantly due to individual factors, mindfulness instruction is an evidence-based approach to counteracting burnout. Our health system initiated a multi-pronged approach to mindfulness instruction for our employees and community. We aimed to assess the impact of these varied programs. Methods: Several mindfulness courses of different lengths were employed. Validated survey instruments were administered to participants before and after the courses to assess stress, mindfulness and burnout. Pre-course and post-course results were compared for each intervention. Free-text responses were also captured and analyzed in a qualitative fashion. Results: Participants in MBIs demonstrated statistically significant improvement in burnout and perceived stress on post-course survey results. Several mindfulness domains also showed statistically significant improvement (awareness, non-react and observe). There was no difference in the observed results between the mindfulness interventions. Qualitative analysis yielded three themes: seeking help, symptoms, and changes in mindfulness practice. Conclusions: MBIs designed for employees of an academic medical center were associated with positive quantitative and qualitative results. All MBI participants achieved improvement in perceived stress and mindfulness as well as reduction in burnout, regardless of course length. Highlights: Several Mindfulness-based interventions were developed and implemented for healthcare employees. These interventions were of varying length, and results were evaluated using validated survey tools. All the interventions were associated with reduced stress and burnout, and improved mindfulness. Course length was not associated with significant changes in these measures.